Changes of Antioxidant Activity in Different Forms and Meal of Arum maculatum in Kahramanmaras Province from Turkey - Sinan Dayisoylu, K. (Asian Journal of Chemistry, 2010)
The meal of Arum maculatum is known in traditional therapy that has many therapeutic effects on human health. In this study, it has been aimed to study the changes in the antioxidant activity of Arum maculatum in different process and consumption models. Also, the antioxidant effect in varying leaf, different forms and the meal of Arum maculatum was investigated. Plants were collected for four forms as fresh (group 1, 2, 3 and 4) and as meal. Antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT) in various leaf forms and meal were measured spectrophotometrically. The activities of SOD and CAT in fresh leaves of A. maculatum's from various locations and their meal were measured. In the study, the results of SOD and CAT of the fresh samples were found as follows: 17.73 ± 7.48 U/mg protein and 13.55 ± 4.30 U/mg protein for group1, 25.05 ± 12.28 U/mg protein and 21.65 ± 4.96 U/mg protein for group 2, 19.86 ± 6.78 U/mg protein and 22.07 ± 4.01 U/mg protein for group 3 and 19.57 ± 6.89 U/mg protein and 22.38 ± 3.41 U/mg protein group 4, respectively. At the same time, CAT and SOD values of the meal,were determined as 20.59 U/mg protein and 62.77 U/mg protein, respectively. SOD activity of the meal was almost three-fold higher than the leaves of A. maculatum. Additionally, CAT activity of the meal was similar to the leaves. The best values for CAT and SOD in the leaves were obtained at -20 °C for 30 days. As a result, the meal and leaves of Arum maculatum could be possessed of antioxidant activity and beneficial effects on human health and nutrition.